Critical Witnessing as a Critical Literacy Practice in Secondary English Education. Issue 1 (2nd January 2023) - Adair, Laura V.; Kim, Grace MyHyun
ABSTRACT: High rates of adolescent depression and anxiety indicate the current need to prepare and support secondary teachers in being responsive to students' emotional and mental health. This article advances a view of secondary English teachers as critical witnesses of adolescent trauma. Through reviewing what critical witnessing is, highlighting the creativity and expertise of literacy educators who practice critical witnessing, naming core stances that critical witnessing asks of teachers, and discussing challenges of doing this work in secondary English classrooms, this article presents critical witnessing as a critical literacy practice that can help facilitate social transformation in secondary English education.